qDATA - an R application implementing a practical framework for analyzing quantitative real-time PCR data - Adrian Ionascu; Alexandru Al. Ecovoiu; Mariana Carmen Chifiriuc; Attila Cristian Ratiu (BioTechniques)
Gene expression assays that are based on quantitative real-time PCR (qRT-PCR) method are still very popular, therefore, we developed qDATA, an open-source R-based bioinformatics application that offers a quick and intuitive analysis of raw cycle threshold (Ct) values. The application relies on a straightforward data input consisting in Ct values and on other mandatory fields specifying the experimental and control groups. qDATA automatically performs descriptive statistics, normality and statistical testing on 2–ΔCt (or ΔCt) and 2–ΔΔCt terms calculated with Livak’s method. We also propose a qRT-PCR data analysis framework that depends on performing exhaustive ΔCt calculations within discrete biological replicates (BRs) and subsequently using the Livak formula for the complete sets of available data. These prerequisites arguably lead to an improved data analysis and statistical relevance. The efficiency of our computing approach was tested using input Ct values corresponding to immune related gene expression evaluated in experimental infection of Drosophila melanogaster and Apis mellifera workers. The presented results reveal that our working strategy is reliable and highlight the efficacy and performance of qDATA application.